Increased Expression of Pregnancy Up-Regulated Non-Ubiquitous Calmodulin Kinase Is Associated with Poor Prognosis in Clear Cell Renal Cell Carcinoma - Wu, Song (Public Library of Science, 2013)
PURPOSE: The aims of this study were to evaluate the clinical significance and potential prognostic value of pregnancy up-regulated non-ubiquitous calmodulin kinase (PNCK) in clear cell renal cell carcinoma (ccRCC) patients. MATERIALS AND METHODS: The expression of PNCK mRNA was determined in 24 paired samples of ccRCCs and adjacent normal tissues using real-time RT-PCR. The expression of PNCK was determined in 248 samples of ccRCCs and 92 paired samples of adjacent normal tissues by immunohistochemical analysis. Statistical analysis was performed to define the relationship between PNCK expression and the clinical features of ccRCC. RESULTS: The mRNA level of PNCK was significantly higher in tumorous tissues than in the adjacent non-tumorous tissues (p<0.001). An immunohistochemical analysis of 92 paired tissue specimens showed that PNCK expression was higher in tumorous tissues than in the adjacent non-tumorous tissues (p<0.001). Moreover, there was a significant correlation between the PNCK expression and various clinicopathological parameters such as Fuhrman grade (p = 0.011), tumor size (p<0.001), T stage (p<0.001) and N stage (p = 0.015). Patients with higher PNCK expression had shorter overall survival time than those with lower PNCK expression (p<0.001). Multivariate analysis indicated that PNCK expression was an independent predictor for poor survival of ccRCC patients. CONCLUSIONS: To our knowledge, this is the first study that determines the relationship between PNCK and prognosis in ccRCC. We found that increased PNCK expression is associated with poor prognosis in ccRCC. PNCK may represent a novel prognostic marker for ccRCC.